The nature of Roman poetry - Williams, Gordon (London [etc.] : Oxford university press, 1970)
Iz predgovora: This book is an abbreviated and simplified version of "Tradition and Originality in Roman poetry", published at the Clarendon press in 1968.
Bibliografija: str. 183-186.
Kazalo
Keywords: rimska poezija; rimska književnost - poezija